CO 5 - CONTINUOUS SPINAL ANAESTHESIA AS AN ADVANCED POSTOPERATIVE CARE PRESERVING STRATEGY: A CASE-REPORT - Ana Patrícia Pereira1,; Francisco Teixeira1,; Diana Roriz1,; Delilah Gonçalves1,; Elisabete Pereira1,; José Carlos Sampaio1, (Journal of the Portuguese Society of Anesthesiology, 2023)
.